Caecal intussusceptions and typhlocolitis in horses with severe Gastrodiscus aegyptiacus infestation. (13th March 2017) - Gratwick, Z.; Donnellan, C.; Page, P. C.; Viljoen, A.; Williams, J.; Lyle, C. H.
Summary: The intestinal trematode Gastrodiscus aegyptiacus ( G. aegyptiacus ) has been recognised in equids around the world for many years, but its pathogenicity is yet to be confirmed. This report describes seven cases of severe G. aegyptiacus infestation, including six cases of caecal intussusception.